The Role of the International Labour Organization (ILO) in the Protection of the Human Rights of Indonesian Migrant Workers - Anisa Sartika Madaniyah; Diandra Putri Sophianandita; Pradindha Tasya Irawan; Yumi Lestari Silalahi (Pt. Anagata Sembagi Education, 2024)
As we know, Indonesians themselves have a fairly high level of competitiveness in terms of employment, which makes it quite difficult to get a job in the country. The minimality of employment makes many Indonesians choose to complain about their fate in another country, often referred to as migrant workers. Indonesia is one of the countries that has a considerable number of migrant workers and is scattered around the world. However, many of the Indonesian migrant workers have experienced human rights violations from their employers, such as discrimination, sexual harassment, physical and mental violence, wage withholding, and even unpaid wages. Human rights are inherent rights of every individual as long as they exist, including the right to education, freedom of religion, access to health facilities, the right to work, and other rights. To address the violations of migrant workers' rights, Indonesia joined the International Labour Organization (ILO), which is under the umbrella of the United Nations, as a reservoir that serves to provide protection for migrants. The ILO also protects workers' rights by improving living standards, hiring policies, working hours, working contracts, health care for workers, and dealing with all workers who have or are experiencing employment problems.